low-grade myofibroblastic sarcoma in the oral cavity: case report (Salud, Arte y Cuidado, 2026)
Objective: To describe the evolution and diagnosis, as well as the registration of a case of a female patient with low-grade myofibroblastic sarcoma in the upper alveolar rim. Clinical case: 36-year-old female, who has been reporting for 2 years an exophytic injury at the level of the upper alveolar rim which has grown progressively, associated over time with dysphagia to solids and liquids; they undergo a lesion biopsy which reports oral Telangiectatic Granuloma, without evidence of malignancy. Neck tomography is performed with contrast, in which a lithic-like lesion is observed that involves the upper jaw with compromise of the bilateral alveolar edge, it is decided to perform a new biopsy and immunohistochemical study, which reports Chronic Xantogranulomatous Inflammation. Patient who is referred to the Otorhinolaryngology Outpatient Consultation of the Central University Hospital Dr. Antonio María Pineda of Barquisimeto Edo. Lara - Venezuela, who is seen at the clinic and presents 2 anatomopathological studies that report chronic inflammation without evidence of malignancy, proceeds to be admitted for exeresis of said injury. The entire sample is taken to anatomopathology, which reports a malignant mesenchymal neoplasm consisting of abundant fusiform cells, findings compatible with low-grade Myofibroblastic Sarcoma. Extension studies are performed without evidence of metastases. Patient with satisfactory evolution at 6 months of his surgery without recurrence. Discussion: The histopathological similarity of LGMS to various benign and reactive tumors can lead to erroneous diagnoses and treatments. The rarity of the LGMS explains the lack of established treatment protocols. Conclusion: This case demonstrates the importance of making appropriate clinical decisions, experience in rare tumor histopathology, and interdisciplinary exchange to achieve cutting-edge patient management.
Keywords: Sarcoma; myofibroblasts; oral cavity